Pesca artesanal e meio ambiente em áreas de manguezais no Complexo Estuarino-costeiro de Itamaracá, Pernambuco: o caso de Itapissuma - Quinamo, Tarcísio dos Santos (2006)
The research focuses on artisanal fishing in the área of Canal de Santa Cruz, Pernambuco North coast, Brazilian Northeast region, specifically in the fishery community of Itapissuma. It deals with that kind of fishing, its interactions inside local estuaries and mangroves ecosystems, as well as the conflicts due to the use of natural resources. The study analyzes that activity taking into account the wider context of socio-economic and socio-environmental changes in the region, particularly in the municipality of Itapissuma (22,000 inhabitants) which belongs to Great Recife, an area of population and economy expansion, and where fishery constitutes the main activity to asure employment, income, and livelihood. The study is based on scientific works on development and sustainability; on estuary and mangrove systems, their importance and dynamics; and on artisanal fishing as well. The information sources include primary data obtained through interviews to a sample of fishers and their families in Itapissuma during the year of 2005; direct observation and seminars/workshops with the participation of members if the local community in order to discuss this research preliminary results. Other sources have been: demographic censuses (years 1991 and 2000); data produced by a previous research on artisanal fishing in the same area (1996); besides photographs, maps, ortophotoes, and satelite images (1988 and 2005). There were also analyzed the changes held inside the fishing community between 1996 and 2005, as well as similar and different characteristics between fishers community and the local population as a whole, taking into account levels of education, income and consumership, age, among others. Discussions took place with the population regarding the main environmental problems connected to fishery. The participants also analyzed the importance of artisanal fishing for employment, income, and production of food for several local communities. As a result of that process, it was found that artisanal fishing in Itapissuma involves about 3.3 thousand men and women that fish and collect small fishes, molluscs, crustaceans, and shellfishes, and that their activity is present in about 50% of all homes, which is a guarantee of work, income, and livelihood. It is also clear that fishery suffers and changes due to following causes: population and urban growing, unemployment, expansion of constructed productive structure and its implications to estuaries and mangroves, whose rich biodiversity supports fishery. Among the environmental problems that affect fishing activity, it can be pointed out: predatory fishery, polution caused by domestic and industrial effluents, destruction of mangrove areas, and presence of motor boats in fishing zones The growing touristic activity and the implementation of the breeding of crabs that receives significant governmental stimulous, are new features in the studied area, that press coast ecosystems as well as show a contrast to the invisibility of fishing activity and of thousands of people who take part and depend on it